1994
DOI: 10.1002/bjs.1800810945
|View full text |Cite
|
Sign up to set email alerts
|

Colectomy and ileorectal anastomosis in patients with Crohn's disease

Abstract: Eighty-three patients underwent colectomy and ileorectal anastomosis for Crohn's disease of the large bowel. There were two postoperative deaths and seven anastomotic leaks. Fifty-two patients retained a functioning anastomosis with a mean follow-up of 8 years. Forty had an excellent or good functional result. The cumulative proportion of patients with a functioning ileorectal anastomosis was 77 and 63 per cent at 5 and 10 years respectively. Patients presenting with perforating Crohn's disease had a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…Rieger et al 26 found that 47 per cent of patients with Crohn's disease required an ileostomy after IRA. Chevalier et al 27 reported that only 51 per cent of their patients with Crohn's disease retained a functioning anastomosis. Melville et al 28 found that 84 per cent of patients with ulcerative colitis who underwent colectomy and IRA still had a functioning anastomosis.…”
Section: Functional Outcomementioning
confidence: 99%
“…Rieger et al 26 found that 47 per cent of patients with Crohn's disease required an ileostomy after IRA. Chevalier et al 27 reported that only 51 per cent of their patients with Crohn's disease retained a functioning anastomosis. Melville et al 28 found that 84 per cent of patients with ulcerative colitis who underwent colectomy and IRA still had a functioning anastomosis.…”
Section: Functional Outcomementioning
confidence: 99%
“…The septic complication rate after strictureplasty was similar or lower to that (3-50 percent) after bowel resection for Crohn_s disease. [82][83][84][85][86][87][88][89][90][91] Other complications included hemorrhage, ileus, wound infection, and bowel obstruction, but their incidence was low. Although major hemorrhage was rare, several patients, especially after multiple strictureplasties, required angiography to identify the bleeding site and intra-arterial vasopressin infusion.…”
Section: Jejunoileal Strictureplastymentioning
confidence: 99%
“…The complication rate after ileocolonic strictureplasty was similar to that after bowel resection. [87][88][89][90][91][92][93][94][95][96] The long-term Vol. 50,No.…”
Section: Ileocolonic Strictureplastymentioning
confidence: 99%
“…A few previous studies report favourable outcome after segmental resection in Crohn colitis, but most report predominantly extensive resection, i.e. total colectomy or proctocolectomy (16)(17)(25)(26)(27)(28)(29)(30)(31)(32). We found similar reoperation rates in patients reconstructed with an anastomosis, regardless of whether the primary procedure was segmental resection or total colectomy.…”
Section: Discussionmentioning
confidence: 99%